The Efficacy of an Expressive Arts-Based Counseling Intervention in Improving Resilience and Well-being of Parents of Children with Intellectual Disabilities in Bangkok: A Mixed Methods Design - Sardar, Afsheen; Mohanan, Santhosh Ayathupady; Ganeshsundaram, Revathi (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
Persons with disabilities face various obstacles in their daily lives and among them, children suffer the most. Consequently, parents of children with intellectual disabilities (CID) often experience a range of uncomfortable emotions associated with their children’s disability, and their own well-being is usually overlooked. Many schools try to alleviate the stress of the children but overlook that of the parents. Although Expressive Arts-Based Counseling (EABC) interventions have been used to help parents of other populations, such interventions have not been used with parents of CID, especially in Thailand. The present study tested an EABC intervention for parents of CID through an explanatory sequential mixed methods research design. The Quasi experimental research design assessed the perceived social support, resilience, self-efficacy, and well-being of 11 parents in the experimental group and 13 parents in the control group. A repeated measures ANOVA was performed to compare the efficacy of the EABC interventions. A comparison of the pre- and post-test results found that resilience and parent well-being had improved significantly. Conversely, perceived social support and parental self-efficacy did not improve with the EABC intervention. The qualitative research with four parents participating in semi-structured interviews helped to establish the potential for the improvement of parental self-efficacy and social support factors. Three important themes emerged: Qualities of the therapeutic environment, the therapeutic process, and validation, coping, and application of the therapeutic insights. Hence an important implication of the study was that EABC interventions could be encouraged with parents and children in special needs schools.